VIOLENCE AND SCHOOLING IN THE PERUVIAN EDUCATIONAL SYSTEM - Gómez Gallardo, Luz Marina (2014)
This article intends to raise awareness of the importance of proposing alternative solutions to a latent problem in Peruvian society which is violence, something that has become a matter of reasonable concern. There are serious and even tragic events that take in the school place, a basic institution that is forming the future citizens, these incidents can manifest in many and can be of public knowledge. This causes uneasiness in some sectors of the community and surprise in others, it is a global phenomenon, and therefore, the responsible is not only the school but also society as a whole.